1993
DOI: 10.1021/bi00064a034
|View full text |Cite
|
Sign up to set email alerts
|

Proton NMR spectroscopic studies of selenosubtilisin

Abstract: Anomalously low-field signals in 1H NMR spectra of serine proteases provide valuable information on the protonation state of the catalytic histidine residue. We have examined the pH dependence of the deshielded protons of three different oxidation states of selenosubtilisin, a semisynthetic selenoenzyme with significant peroxidase activity, in order to evaluate the influence of the selenium prosthetic group on the hydrogen-bonding network in the modified active site. In the spectra of the anionic seleninate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 26 publications
2
23
0
Order By: Relevance
“…The crystal structure of selenosubtilisin shows that it is in the seleninic acid form (Enz-SeO 2 − ) (Syed et al 1993). NMR studies of selenosubtilisin show that it also exists in the selenenic acid (Enz-SeOH) and selenosulfide (Enz-Se-SR) forms (House et al 1993). If our hypothesis is incorrect, then the Enz-SeO 2 − form should be inactive, however, all three forms of selenosubtilisin have peroxidase activity (Bell et al 1993).…”
Section: Evidence For Our Hypothesis From the Study Of Selenosubtilisinmentioning
confidence: 99%
“…The crystal structure of selenosubtilisin shows that it is in the seleninic acid form (Enz-SeO 2 − ) (Syed et al 1993). NMR studies of selenosubtilisin show that it also exists in the selenenic acid (Enz-SeOH) and selenosulfide (Enz-Se-SR) forms (House et al 1993). If our hypothesis is incorrect, then the Enz-SeO 2 − form should be inactive, however, all three forms of selenosubtilisin have peroxidase activity (Bell et al 1993).…”
Section: Evidence For Our Hypothesis From the Study Of Selenosubtilisinmentioning
confidence: 99%
“…Generally it is well established that exposed selenols are a very reactive species and readily oxidised by air [110]. 1 H-NMR studies of selenoenzyme selenosubtilisin revealed that the enzyme-bound selenol and seleninic acid have unusually low pK A values when compared to typical selenium compounds and were found to be deprotonated at all accessible pHs [111]. Intriguingly, Sec residues in peptides are found to be fully oxidised directly upon deprotection via hydrogen fluoride [27] (Metanis N, Dawson PE.…”
Section: Pk a Nucleophilicity And Reactivitymentioning
confidence: 99%
“…Although the proposed catalytic mechanism, which involves two cycles and six intermediates, is significantly different from that of GPX, the obvious enhancement of GPX-like activity observed by introducing an amino nitrogen near the divalent selenium, strongly indicates the importance of the amino groups located in the vicinity of the diselenide bond. Hilvert et al [91][92] have reported that an artificial enzyme selenosubtilisin, possessing a strongly basic histidine residue at the active center like Wilson's catalyst, exhibits high GPX-like activity. They concluded that the protonated histidine acts as a general acid facilitating the reduction of the selenenyl sulfide to selenolate with thiols.…”
Section: B Compounds With Indirect Se-n Bond Interactionmentioning
confidence: 99%
“…The selenol, like the seleninic acid, is known to have an unusually low pKa value from spectroscopic titration of its 77 Se resonance, and its departure from the selenenyl sulfide is expected to be facilitated by protonation of the active site histidine. The resulting selenolate-imidazolium ion pair is quite stable over the pH range 4-10, and protonation of an active site residue (pK a≈7) has been shown to be necessary for efficient turnover catalysis [91][92].…”
Section: (C) Engineering Naturally Occurring Enzymes Into Selenoenzymesmentioning
confidence: 99%